Halal Literacy and Halal Cosmetic Purchase Decisions among Nurul Jadid University Students: Evidence from Shopee Users - Muhammad Athoillah; Mufidatul Himmah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The rapid growth of digital marketplaces has transformed consumer purchasing behavior, including the consumption of halal cosmetic products. In online shopping environments, halal literacy has become an important factor as consumers are required to evaluate product information independently. This study aims to examine the influence of halal literacy on cosmetic purchase decisions among Nurul Jadid University students who use the Shopee platform. A quantitative associative approach was employed, involving 60 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed through simple linear regression with SPSS version 25. The findings indicate that halal literacy has a positive and significant effect on purchase decisions, with a correlation coefficient (R) of 0.724 and a coefficient of determination (R²) of 0.525. The t-test results (t = 8.004; p < 0.001) further confirm this relationship. These findings highlight the important role of halal literacy in promoting responsible purchasing decisions and contribute to the growing literature on halal consumer behavior in digital marketplace environments